Markers of Increased Cardiovascular Risk in Postmenopausal Women: Focus on Oxidized-LDL and HDL Subpopulations - Mascarenhas-Melo, Filipa (Hindawi Publishing Corporation, 2013)
Objective. To evaluate the effect of gender and menopause in cardiovascular risk (CVR) in a healthy population based on both classical and nontraditional markers. Methods. 56 men and 68 women (48 pre- and 20 postmenopause) were enrolled in the study. The following markers were analyzed: blood pressure (BP), body mass index (BMI), waist circumference (WC), glucose, total cholesterol (total-c), triglycerides (TGs), low-density lipoprotein cholesterol (LDL-c), oxidized-LDL (Ox-LDL), HDL-c and subpopulations, paraoxonase-1 activity, hsCRP, uric acid, tumor necrosis factor alpha (TNF-α), adiponectin, vascular endothelial growth factor (VEGF), and intercellular adhesion molecular 1 (ICAM1). Results. Relative to the women, men present significantly increased BMI, WC, BP, glucose, total-c, TGs, LDL-c, Ox-LDL, uric acid, and TNF-α and reduced adiponectin and total and large HDL-c. The protective profile of women is lost after menopause with a significantly increased BMI, WC, BP, glucose, LDL-c, Ox-LDL, hsCRP, and VEGF and decreased total and large HDL-c. Significant correlations were found in women population and in postmenopausal women between Ox-LDL and total, large, and small HDL-c and between TNF-α and total, large, and small HDL-c, LDL-c, and Ox-LDL. Conclusions. Men present higher CVR than women who lost protection after menopause, evidenced by nontraditional markers, including Ox-LDL and HDL subpopulations.